Ptf1a inactivation in adult pancreatic acinar cells causes apoptosis through activation of the endoplasmic reticulum stress pathway - Sakikubo, Morito (Sci Rep, 2018)
Pancreas transcription factor 1 subunit alpha (PTF1A) is one of the key regulators in pancreatogenesis. In adults, it transcribes digestive enzymes, but its other functions remain largely unknown. Recent conditional knockout studies using Ptf1a(CreER/floxed) heterozygous mouse models have found PTF1A contributes to the identity maintenance of acinar cells and prevents tumorigenesis caused by the oncogenic gene Kras. However, Ptf1a heterozygote is known to behave differently from homozygote. To elucidate the effects of Ptf1a homozygous loss, we prepared Elastase-CreERTM; Ptf1a(floxed/floxed) mice and found that homozygous Ptf1a deletion in adult acinar cells causes severe apoptosis. Electron microscopy revealed endoplasmic reticulum (ER) stress, a known cause of unfolded protein responses (UPR). We confirmed that UPR was upregulated by the activating transcription factor 6 (ATF6) and protein kinase RNA (PKR)-like endoplasmic reticulum kinase (PERK) pathways, but not the inositol requiring enzyme 1 (IRE1) pathway. Furthermore, we detected the expression of CCAAT-enhancer-binding protein (C/EBP) homologous protein (CHOP), a pro-apoptotic factor, indicating the apoptosis was induced through UPR. Our homozygous model helps clarify the role PTF1A has on the homeostasis and pathogenesis of exocrine pancreas in mice.